Moving finite element method : fundamentals and applications in chemical engineering /: fundamentals and applications in chemical engineering. (2016) - Coimbra, Maria do Carmo; Rodrigues, Alírio E; Rodrigues, Jaime Duarte; Robalo, Rui Jorge Mendes; Almeida, Rui Manuel Pires
No abstract available